A model for implementation of IT service management in Zimbabwean state universities - Zhou, Munyaradzi; Ruvinga, Caroline; Musungwini, Samuel; Zhou, Tinashe G. (International Journal of Computer Science and Business Informatics, 2017)
Several IT service management (ITSM) frameworks have been deployed and are being adopted by companies and institutes without redefining the framework to a model which suits their IT departments’ operating environment and requirements. An IT service management model is proposed for Zimbabwean universities and is a holistic approach through integration of Operational Level Agreements (OLAs), Service Level Agreement (SLAs) and IT Service Catalogues (ITSCs). OLA is considered as the domain for describing IT Service management and its attainment is geared by organizational management and IT section personnel in alignment with the mission, vision and values of the organization. Explicitly defining OLAs will aid management in identification of key services and processes in both qualitative and quantitative form (SLAs). After defining SLAs then ITSCs can be formulated, a measure which is both customer and IT service provider centric and acts as the nucleus of the model. Redefining IT Service Management from this perspective will result in deriving value from IT service management frameworks and customer satisfaction.